Moderating effects of MNCs’ size in the relationship between knowledge characteristics and degree of inter-firm technology transfer in international joint ventures - Sazali Abdul Wahab; Raduan Che Rose; Haslinda Abdullah; Jegak Uli (EuroJournals Publishing, 2009)
The main objective of this paper is to empirically examine the moderating effect of size of MNCs on the relationships between knowledge characteristics: tacitness, complexity and specificity and two distinct dimensions of degrees of technology transfer: degrees of tacit and explicit knowledge in inter-firm technology transfer within IJVs. Using the moderated multiple regression, the theoretical models and hypotheses in this study were tested based on empirical data gathered from 128 joint venture companies registered with the Registrar of Companies of Malaysia (ROC). The results revealed that size of MNCs has significantly affected the relationships between knowledge characteristics (tacitness, complexity and specificity) and both degrees of tacit and explicit knowledge; where the relationships were found stronger for medium/small MNCs than large MNCs. The study has bridged the literature gaps in such that it offers empirical evidence on the moderating effect of size of MNCs on the relationships between knowledge characteristics and two distinct degrees of technology transfer: degrees of tacit and explicit knowledge using the Malaysian sample.